PKM Trauma Healing Pasca Letusan Gunung Semeru di Kabupaten Lumajang - Prima Soultoni Akbar (Yayasan Daarul Huda Kruengmane, 2023)
The eruption of Mount Semeru in Lumajang is an unpredictable natural disaster. After experiencing this event, the victim can be very shocked and experience extraordinary trauma. Long-term effects, such as unexpected emotions, feelings of tension, physical symptoms, or other strange symptoms. Not infrequently, these symptoms even greatly interfere with the daily activities of the victims. Trauma healing for residents who experience difficult times due to the disaster needs to be done. This is because they tend to be haunted by excessive anxiety when the disaster comes again. Trauma healing can be the right rehabilitation step for disaster victims to be able to heal themselves from heartbreaking tragedies after a disaster. One of the trauma healing educational methods used in this activity is psychological education which educates victims about PTSD symptoms and the various treatments available. The role of Pormiki DPC Malang in trauma healing is to be able to divert bad thoughts from disasters so that residents are not dragged into grief and can learn from it.